Challenges of pre-hospital emergency care at Addis Ababa Fire and Disaster Risk Management Commission, Addis Ababa, Ethiopia: a qualitative study - Feleku Yimer Seid; Birhanu Chekol Gete; Amanuel Sisay Endeshaw (BMC, 2024)
Abstract Background A challenge to pre-hospital emergency care is any barrier or obstacle that impedes quality pre-hospital care or impacts community pre-hospital utilization. The Addis Ababa Fire and Disaster Risk Management Commission (AAFDRMC) provides pre-hospital emergency services in Addis Ababa, Ethiopia. These services operate under a government-funded organization that delivers free emergency services, including out-of-hospital medical care and transportation to the most appropriate health facility. This study aimed to assess the challenges of pre-hospital emergency care at the Addis Ababa Fire and Disaster Risk Management Commission in Addis Ababa, Ethiopia. Methods A qualitative descriptive study was conducted from November 20 to December 4, 2022. Data were collected through in-depth, semi-structured interviews with 21 experienced individuals in the field of pre-hospital emergency care, who were selected using purposeful sampling. A thematic analysis method was used to analyze the data. Results This study includes twenty-one participants working at the Addis Ababa Fire and Disaster Risk Management Commission. Three major themes emerged. The themes that arose were the participants' perspectives on the challenges of pre-hospital emergency care in Addis Ababa, Ethiopia. Conclusion and recommendation The Fire and Disaster Risk Management Commission faces numerous challenges in providing quality pre-hospital emergency care in Addis Ababa. Respondents stated that infrastructure, communication, and resources were the main causes of pre-hospital emergency care challenges. There has to be more focus on emergency management in light of infrastructure reform, planning, staff training, and education, recruiting additional professional power, improving communication, and making pre-hospital emergency care an independent organization in the city.